The determinants of farm income variability: Evidence from Estonia - Olha Aleksandrova; Hossein Azadi; Rando Värnik; Maire Nurmet; Ants-Hannes Viira (German Journal of Agricultural Economics (GJAE), 2024)
Farm income is a policy-relevant proxy for farm households' viability. Volatile income levels reduce the well-being of farmers and decrease their incentives to produce, invest, and innovate. This article provides a comprehensive analysis of the associations between agricultural subsidies, farm characteristics, and the stability of farm income, along with their relative importance, by applying a linear fixed-effects model to the Estonian Farm Accountancy Data Network (FADN) sample. Building on previous analyses, we show that a significant portion of agricultural subsidies in gross farm income is positively associated with income instability. Our estimates suggest that financial immobility is positively correlated with income stability. This indicates that farm-specific grants can provide opportunities to invest while also alleviating budget constraints for indebted farms. After controlling for various farm characteristics, we find that income becomes more stable as farmers age, while income volatility associated with agricultural production is positively linked to rising land prices.
Keywords: 330; Agricultural Subsidies; Agriculture; Estonia; Farm Income Instability; Within Instrumental Variables Estimator